2014
DOI: 10.7314/apjcp.2014.15.16.6863
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Diabetic Medications Do Not Influence Risk of Lung Cancer in Patients with Diabetes Mellitus: a Systematic Review and Meta-analysis

Abstract: Objectives: Several preclinical and observational studies have shown that anti-diabetic medications (ADMs) may modify the risk of lung cancer. We performed a systematic review and meta-analysis evaluating the effect of metformin, sulfonylureas (SUs), thiazolidinediones (TZDs), and insulin on the risk of lung cancer in patients with diabetes mellitus (DM

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…However, there are also a few studies that report no effect between metformin and risk of lung cancer. Nie et al reported that in 11 studies found, in a systematic search up to August 2013, there was no significant association between diabetes mellitus patients receiving metformin and lung cancer risk (OR = 0.99, 95% CI: 0.87–1.12) [85]. Similarly, Franciosi et al reported that in two randomized controlled studies (RCTs) and four observational studies, there was no significant association between metformin and lung cancer risk in RCTs and only a marginal non-significant reduction was found in observational studies in diabetes mellitus patients (OR = 0.83, 95% CI: 0.64–1.06, p = 0.13) [86].…”
Section: Effects Of Metformin In Lung Cancer: Human Studiesmentioning
confidence: 99%
“…However, there are also a few studies that report no effect between metformin and risk of lung cancer. Nie et al reported that in 11 studies found, in a systematic search up to August 2013, there was no significant association between diabetes mellitus patients receiving metformin and lung cancer risk (OR = 0.99, 95% CI: 0.87–1.12) [85]. Similarly, Franciosi et al reported that in two randomized controlled studies (RCTs) and four observational studies, there was no significant association between metformin and lung cancer risk in RCTs and only a marginal non-significant reduction was found in observational studies in diabetes mellitus patients (OR = 0.83, 95% CI: 0.64–1.06, p = 0.13) [86].…”
Section: Effects Of Metformin In Lung Cancer: Human Studiesmentioning
confidence: 99%
“…Zhang et al pooled the data from 4 studies and showed a significantly lower risk associated with metformin use (pooled relative risk: 0.71, 95% confidence interval: 0.55-0.95, P =0.02) [24]. However, by including 15 (11 cohort and 4 case-control) observational studies, Nie et al reported a null association with an adjusted odds ratio of 0.99 (95% confidence interval: 0.87-1.12) [25]. The meta-analysis by Wu et al (including 15 studies: 11 cohort, 2 case-control and 2 randomized controlled trials) suggested a 15% risk reduction (odds ratio 0.85, 95% confidence interval: 0.77-0.92), but this could not be demonstrated in smoking-adjusted subgroup [26].…”
Section: Introductionmentioning
confidence: 99%
“…With the development of living standard, the morbidity of type 2 diabetes mellitus (T2DM) increases rapidly (2). At present, numerous studies have found that T2DM is a systemic disease, and associated with the progression of several human malignant tumors (3,4). …”
Section: Introductionmentioning
confidence: 99%